ИНТЕРПРЕТАЦИИ ГЕШТАЛЬТА В СОВРЕМЕННОЙ ПОПУЛЯРНОЙ КУЛЬТУРЕ - КОЛЫЧЕВА, Т. В.; ЛЕБЕДЕВ, В. А. (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science", 2015)
В статье анализируется феномен гештальта в ракурсе рассмотрения закономерностей сюжетов современной популярной культуры. Делается вывод о том, что мышление человека посредством образования форм является естественным, в связи с чем создатели массовой культуры именно в такой интерпретации доносят до зрителя свои сюжеты. Т.В. Количева, В.О. Лебедєв ІНТЕРПРЕТАЦІЇ ГЕШТАЛЬТУ В СУЧАСНІЙ ПОПУЛЯРНІЙ КУЛЬТУРІ В статті аналізується феномен гештальту в ракурсі розгляду закономірностей сюжетів сучасної популярної культури. Робиться висновок про те, що мислення людини за допомогою створення форм є природним, в зв’язку з чим в масовій культурі саме в такий інтерпретації сюжети масової культури доносяться до глядача. Ключові слова: гештальт, популярна культура, образ, ціле, частина. T. V. Kolycheva, V. A. Lebediev THE INTERPRETATION OF THE GESTALT IN MODERN POPULAR CULTURE The article analyzes the phenomenon of Gestalt from the perspective of consideration of laws of subjects of contemporary popular culture. The relevance of the topic is associated with the increasing necessity of expansion of the instruments of knowledge and selfknowledge, and with the possibility to apply the concept of the Gestalt of the modern popular culture. The purpose of this paper is the demonstration of the manifestations of the Gestalt in modern popular culture. The idea of the Gestalt are based on the criticism of Associationism. Direction of the gestaltpsychology formed under the direct influence of phenomenology, which States that the perception of the world is holistic, structured character. Any reality, which is constructed from gestalts - this is the reality that the subject realized, and then described and interpreted. Affirms, that the Gestalt can be represented as a whole, consisting of some Autonomous parts. And in this connection it is interesting to analyze the following feature, characteristic for the modern popular culture. In it at different levels is very popular subject in which there is a powerful artifact that gives its possessor the immense power (as an option - able to awaken the ancient mechanism, a monster or a deity), but was defeated in ancient times into several parts. Connect them together can bring to the world or deliverance from evils, or, on the contrary, cause catastrophic. The development of such work due to the fact that the heroes collect entire artifact, looking for its components and parts. The article concludes that the human mind tends to education forms, configurations, and on examples of subjects of contemporary popular culture, you can see that the streamlining of the diversity of individual elements help to create new objects. Key words: gestalt, popular culture, image , as a whole, part .